A CONTRIBUTION TO THE KNOWLEDGE OF THE DRAGONFLIES (ODONATA) FROM THE RIVER MORAČA (MONTENEGRO) (Acta Entomologica Serbica, 2010)
Fauna of dragonflies (Odonata) of the Morača River (Montenegro) was studied during 2007 and 2008. Samples were collected in five localities along the river. Examined sites provide specific living conditions of differently adopted species of dragonflies. During the study 934 individuals classified into 35 species were collected. One of them, Trithemis annulata (Palisot de Beauvois, 1805), was collected for the first time and thereby confirmed the record of this species for fauna of Odonata in Montenegro.